2009
DOI: 10.1002/dc.21207
|View full text |Cite
|
Sign up to set email alerts
|

Modified fine‐needle aspiration technique for diagnosis of granulomatous skin lesions with special reference to leprosy and cutaneous tuberculosis

Abstract: Skin infections are commonly assessed by slit skin or scrape methods. Fine-needle aspiration biopsy (FNAB) is highly effective especially with blanching of skin to ensure good yield and reduced bleeding. The aim of this study was to assess usefulness of cytology, especially modified FNAB technique, in diagnosis of leprosy and cutaneous tuberculosis and to identify specific cytological characteristics for diagnosis and classification. The study was conducted on 40 patients-25 cases of leprosy and 15 cases of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…Katuria et al found similar correlation of 94.8% in scrofuloderma, 88.9% in lupus vulgaris and an overall correlation of 92.9% on cytopathology compared to histopathology with 30 cases using modified FNA technique . Mehdi et al also found a correlation of 80% with a sample size of 11 cases . Hence doing FNA is advantageous in cutaneous tuberculosis as it shows high correlation to histopathology, it is less time consuming, more compliant and cost effective.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Katuria et al found similar correlation of 94.8% in scrofuloderma, 88.9% in lupus vulgaris and an overall correlation of 92.9% on cytopathology compared to histopathology with 30 cases using modified FNA technique . Mehdi et al also found a correlation of 80% with a sample size of 11 cases . Hence doing FNA is advantageous in cutaneous tuberculosis as it shows high correlation to histopathology, it is less time consuming, more compliant and cost effective.…”
Section: Discussionmentioning
confidence: 89%
“…Mehdi et al also concluded that distinguishing various subtypes of cutaneous tuberculosis is difficult on the basis of cytology alone. Clinical correlation is essential to arrive at a final diagnosis …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations